Morphological characteristics of the limbal epithelial crypt. Issue 4 (4th October 2006) - Shanmuganathan, Vijay A; Foster, Toshana; Kulkarni, Bina B; Hopkinson, Andrew; Gray, Trevor; Powe, Des G; Lowe, James; Dua, Harminder S
Abstract : Aim: In 2005 we reported the discovery of a novel anatomical structure at the limbus, which we termed the limbal epithelial crypt (LEC). The purpose of this study was to further evaluate the distribution, immunophenotypical, and ultra structural characteristics of the LEC as a putative niche of stem cells. Methods: Sequential histological sections of human corneo-scleral limbal rims were examined for the presence and distribution of the LEC. Immunophenotypical characterisation of the LEC cells using a panel of antibodies of interest was undertaken. Transmission electron microscopy of the LEC was used to examine the ultra structural and morphometric features of cells within the LEC and adjacent limbus. Results: A total of 74 LECs were identified in eight corneo-scleral rims. These varied in number, size and distribution within rims. Cells within the crypt demonstrated the following phenotype: CK3−/CK19+/CD 34−/Vimentin+/p63+/Connexin 43+/MIB1 (Ki67)−. Presence of Cx43 was also demonstrated in the rete pegs adjacent to the LEC. Basal cells of the LEC were significantly smaller than basal cells found in adjacent rete pegs and also smaller than suprabasal limbal and central corneal epithelial cells (p<0.05). Morphologically they had a high nuclear:cytoplasmic ratio and were adherent to the underlying basement membrane by means of complex convolutions of cytoplasmic processes. Conclusions: LECs are sparse but a consistent finding in the human corneo-scleral limbus. The LEC contains a unique sub-population of cells expressing several characteristics that are consistent with it representing a putative stem cell niche.